Ultrasonic Damage Assessment Using Virtual Time Reversal Indices and the RAPID Method - de Castro, Bruno Albuquerque [UNESP]; Baptista, Fabricio Guimarães [UNESP]; Ciampa, Francesco (Springer Nature, 2023)
Ultrasonic methods for damage imaging typically use baseline signals from the undamaged part, which are often affected by real operational conditions and may not always be available. This paper proposes a baseline-free damage imaging algorithm based on a combination of virtual time reversal (VTR) and the Reconstruction Algorithm for Probabilistic Inspection of Damage (RAPID) tomographic technique. VTR is an alternative to traditional time reversal as it reduces the burden of physically back-propagating re-mitted signals by applying signal operations between the transmitted and received waveforms. Spatial VTR-based damage indices were here proposed to enhance defect detection as they do not require the time domain reconstruction of re-emitted signals. Experimental results on damaged aluminium and composite specimens showed that the proposed VTR-based damage indices coupled to the RAPID imaging algorithm were able to localise material flaws with a maximum localisation error of ~6 mm and ~2 mm for aluminium and composite samples, respectively.
Keywords: Baseline-free; Damage imaging; Signal processing; Ultrasound; Virtual time reversal